INFORMATION SYSTEM FOR MANAGING A MULTIMEDIA ONLINE SERVICE FOR LANGUAGE LEARNING - VASYLIUK, ANDRII; STRUS, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
An analysis of terminology for the creation of a multimedia learning resource has been conducted, specifically examining the terms "multimedia," "technology and technology integration," and "multimedia learning resource." The use of this technology in language classrooms has been substantiated. A study has been carried out on the set of multimedia learning resources as an element of modern education. The impact of multimedia use on improving English language learning quality has been explored. An analysis of existing multimedia learning resources for English language acquisition has been conducted.The key principles of foreign language learning through multimedia learning resources have been described, along with the main requirements for multimedia in such resources, including: avoiding excessive accumulation of textual and illustrative information, ensuring a clear order of structural elements, organically supplementing the main text with multimedia objects, maintaining emotional engagement in multimedia, accompanying multimedia objects with explanations, incorporating video clips, and selecting appropriate background music.The main advantages that distinguish this service from existing market solutions have been identified and selected for use in developing a unique and popular multimedia learning resource. These include: user capabilities for tracking learning progress, language study reminders and customizable regular push notifications, gradual and tiered access to relevant information, tools for seamless group collaboration, as well as access to the most popular courses and topics, and individual learning management.